Nuclear magnetic resonance (NMR) spectroscopy of membrane and membrane associated proteins. - Tan, Edward Tzu Kwang. (2013)
Biological membranes serve as essential barriers between living cells and their surroundings, as well as within the living cell, and are seen as primary targets for pharmaceutical and drug development against disease and illness. In order to understand the structure-function relationships of membrane proteins, high resolution three-dimensional (3D) structures are required. Nuclear magnetic resonance spectroscopy is a tool which is used to solve high resolution structures of protein.In this thesis, three membrane/ membrane associated proteins are discussed; 1) the Severe Acute Respiratory Syndrome (SARS) coronavirus envelope (E) protein, 2) the small hydrophobic (SH) protein of the human Respiratory Syncytial Virus (hRSV) and 3) the heme binding PAS domain of YybT from Geobacillus thermodenitrificans.